2000
DOI: 10.1093/her/15.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led and adult-led school health education: a critical review of available comparative research

Abstract: Peer-led health education in school is widely used. Advocates suggest it is an effective method based on the belief that information, particularly sensitive information, is more easily shared between people of a similar age. Critics suggest that this is a method not based on sound theory or evidence of effectiveness. This review evaluates school-based health education programmes which have set out to compare the effects of peers or adults delivering the same material. The identified studies indicated that peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(204 citation statements)
references
References 45 publications
11
175
0
10
Order By: Relevance
“…Our findings corroborate and strengthen earlier reviews, which suggested that the inclusion of peers in public health interventions would have benefits in preventing harmful behaviours during adolescence 17, 18, 28, 56. Our findings also suggest that there may be scope to consider the more extensive trial and implementation of peer‐led intervention models, given current gaps in the evidence base regarding the prevention of substance use among young people.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings corroborate and strengthen earlier reviews, which suggested that the inclusion of peers in public health interventions would have benefits in preventing harmful behaviours during adolescence 17, 18, 28, 56. Our findings also suggest that there may be scope to consider the more extensive trial and implementation of peer‐led intervention models, given current gaps in the evidence base regarding the prevention of substance use among young people.…”
Section: Discussionsupporting
confidence: 88%
“…Our systematic review and meta‐analysis supports previous evidence 18, 27, 28 by highlighting the promise and effectiveness of peer‐led interventions. However, our study goes further in strengthening the evidence by including more recent studies and by providing a quantified estimate of the effect of such interventions in relation to tobacco, alcohol and cannabis use.…”
Section: Implications and Other Evidencesupporting
confidence: 84%
See 3 more Smart Citations